Placenta accreta spectrum, experience in a Peruvian hospital - Ramírez Cabrera, Juan Orestes (2020)
Introduction: Placenta accreta spectrum (PAS) refers to pathological adhesions of the placenta to the uterus. It is considered a public health problem due to its increase in recent decades, and it is associated with significant maternal morbidity and mortality and high risk of hemorrhage, blood transfusions and hysterectomy. Objective: To determine the epidemiological, surgical and post-surgical characteristics of patients with placenta accreta. Methods: Descriptive, retrospective study of patients with placenta accreta spectrum attended at San Bartolomé Hospital, Lima, Peru, between 2014 and 2018. Results: Thirty-six PAS cases were documented with a birth rate of 1.2/1 000; 94% occurred in multiparous women, 81% had previous uterine surgery including 26 (72%) with previous cesarean section; 61% were 35 years old or older, and 47% had placenta previa. Treatment was conservative in 53% of the cases, while hysterectomy was performed in 47%. There were post-surgical complications in 53%, without maternal deaths. Conclusions: In our study, placenta accreta spectrum was predominantly associated with previous cesarean sections. A considerable number of cases presented hemorrhage and hypovolemic shock. Timely surgical intervention and a well-supplied blood bank allowed conservative management in focal accretism as a valid alternative to hysterectomy and its complications.